Penguatan Baca Tulis Alquran Mahasiswa Program Studi Pendidikan Agama Islam IAIN Pekalongan - Dian Rif’iyati (Madaniyah, 2019)
This research was aimed to reveal the strengthening of Baca Tulis Alquran (BTQ) students of Islamic Education Program of IAIN Pekalongan. This research was field research using content analysis. The results of this research revealed that the strengthening of Baca Tulis Alquran (BTQ) students of Islamic Education Program of IAIN Pekalongan through several activities they are: (1) Coordinating with the deputy dean 3 and the BTQ Lecturer Coordinator; (2) Empowering UKM LPTQ in students mentoring who study BTQ; (3) Application of peer tutors in lecture classes; (4) Guiding and training students who do not understand BTQ; (5) Dissemination of internet applications about BTQ; (6) Habituation program in lectures; and (7) Conducting cooperative relations with Islamic boarding schools which located around IAIN Pekalongan. All these activities are carried out for the sake of embedded the tagline of IAIN Pekalongan they are spirituality, scientific, entrepreneurship, and nationality values for every student.